The Influence of MPSAS Values and SQM Angles in Determining Fajr Time in a Mathematical Review - Br Pinem, Rasta Kurniawati; Hidayat, Muhammad; Ananda, Fadhilla Sayu (JMEA : Journal of Mathematics Education and Application, 2024)
In Indonesia, a dip of -20 degrees has been adopted for dawn, which so far has no known scientific reference and indicates that dawn in Indonesia is too early. The results of this research show that the MPSAS value and SQM angle have an influence in determining the time of dawn so that several considerations that can be made in researching the time of dawn using SQM include paying attention to the MPSAS value of a place, the direction of the SQM angle, moonlight, weather, calibration of the SQM tool, data processing methods. etc. Research at Pondok Permai beach shows changes in sky brightness, namely at a sun depth of 15 degrees and research at Sri Mersing beach at 14 degrees. There are differences in the value of changes in sky brightness in SQM which lead to different observation angles, if it is a sunny day the difference is around 0.25-0.75 degrees, whereas if it is a cloudy day the change in the graph at each angle does not remain at an angle of 0 degrees. From the results of the research carried out, there is more often interference in the form of clouds.